NILAI TAMBAH DAN KELAYAKAN USAHA SKALA KECIL DAN SKALA MENENGAH PENGOLAHAN LIMBAH PADAT UBI KAYU (ONGGOK) DI KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR - Cahya Nisa Diach Maharani; Dyah Aring Hepiana Lestari; Eka Kasymir (Lampung University, 2013)
The purposes of this research were to determine value addedand analyze the feasibility of cassava solid waste (“onggok”) processing business.This research was conducted in Pekalongan District,East Lampung Regency in which in two businesses of medium-scale processor and small-scale processor were chosen purposely based on the criteria of MSME (Micro, Small and Medium Enterprises).The primary data was analyzed by calculating the value-added, NPV, IRR, gross B/C ratio, net B/C ratio, and payback period. In addition, the sensitivity analysis was done based on the possibility of cost increase, price reduction, and production decrease.The results showed that the small-scale processorgave larger value-addedthan the medium-scale. Based on market, social, and environmental as well as financial aspects, cassava solid waste processors were profitable and feasible to be developed. These businesses were sensitive to the increase in production cost and the decrease in production.Key words : added value, cassava solid waste, feasibility of bussiness